Bioelectrochemical cells as a green energy source for electrochemical treatment of water and wastewater. (December 2022) - Nidheesh, P.V.; Ganiyu, Soliu O.; Kuppam, Chandrasekar; Mousset, Emmanuel; Samsudeen, N.; Olvera-Vargas, Hugo; Kumar, Gopalakrishnan
Abstract: The quest for renewable energy sources to drive different sectors of the economy has become essential, owing to the continuous depletion of fossil fuels as well as environmental hazards associated with it. Bioelectrochemical cells (BEC), where microbial activities convert the energy stored in the form of carbon in waste to bioenergy, nutrient and value-added chemicals, is seen as an exciting alternative for simultaneous energy production and environmental remediation. BEC have been successively utilized for driving different electrochemical reactors applied in water/wastewater and contaminated soils remediations and nutrient/chemical recovery. This review concisely summarizes the principle, design and applications of BEC as a green energy source for electrochemical treatment of water and wastewater. The various BEC coupled energy systems, critical factors affecting the BEC performance, different BEC coupled electrochemical processes and challenges in scaling-up of coupled systems for long-term performance were critically discussed in this review. Highlights: Energy produced from BEC is an affordable energy source for electrochemical processes. The combined system is able to remove pollutants in a sustainable manner. Both BEC and electrochemical systems are able to remove pollutants.